2005
DOI: 10.1097/01.opx.0000171336.40273.3f
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years in an Urban Low Vision Clinic: Changes in Prescribing Habits of Low Vision Practitioners

Abstract: Between 1973 and 2003, the low vision clinic at Moorfields Eye Hospital provided nearly 100,000 low vision consultations. The demographics of patients attending the clinic remained remarkably constant over this time. The number of spectacle-mounted devices prescribed to new patients fell between 1973 and 2003. It is thought this is in part the result of the increased availability of electronic magnification devices and the development of illuminated hand magnifiers. The development of the acrylic bright field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 10 publications
7
30
2
Order By: Relevance
“…Majority of our patients considered their problemswith near and distance vision to be of equal importance.However, elderly patients were more likely to deem nearvision as being their major problem; while children hada tendency to judge distance vision as more important.This observation perhaps portrays the additional effectof presbyopia on low vision in the elderly, although itmay also signify that the elderly have a greater likelihoodof central visual loss from macular disease.Posterior segment disease accounted for the majorityof causes of low vision in this study. This correlates withfindings of most low vision clinic studies [6,11,12,[14][15][16][17].In our study,the commonestcause was ARMD which is similar to some previous reports who found age related macular degeneration (ARMD) to bethe commonest cause [11,12,17,18].Besides, there are other reports,specifically from developing countries, in which ARMDwas also not the commonest cause [6,[14][15][16]. Possiblereasons for lower prevalence of ARMD in developingcountries may include nutritional factors, less cigarettesmoking, and lower body mass index (BMI) [21].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Majority of our patients considered their problemswith near and distance vision to be of equal importance.However, elderly patients were more likely to deem nearvision as being their major problem; while children hada tendency to judge distance vision as more important.This observation perhaps portrays the additional effectof presbyopia on low vision in the elderly, although itmay also signify that the elderly have a greater likelihoodof central visual loss from macular disease.Posterior segment disease accounted for the majorityof causes of low vision in this study. This correlates withfindings of most low vision clinic studies [6,11,12,[14][15][16][17].In our study,the commonestcause was ARMD which is similar to some previous reports who found age related macular degeneration (ARMD) to bethe commonest cause [11,12,17,18].Besides, there are other reports,specifically from developing countries, in which ARMDwas also not the commonest cause [6,[14][15][16]. Possiblereasons for lower prevalence of ARMD in developingcountries may include nutritional factors, less cigarettesmoking, and lower body mass index (BMI) [21].…”
Section: Discussionsupporting
confidence: 81%
“…This difference in the patternof the age distribution may be a reflection of the oldergeneral populations in developed countries [11,14] andlow life expectancy in developing countries [16].Despite this fact, thedifference may actually be an indication that the [15], and India-2.6:1 [16]. It is, however,different from the pattern in developed countrieswhere more females were found to present for lowvision services [11,12,18]. This probably demonstratesthe reduced access and utilisation of eye care services byfemales in developing countries [19,20].In our study, however, we found that the proportion of females reduced with age,though this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the potential for focus groups to become dominated by one or two individuals, and the potentially personal nature of some of the responses to the question asked, it was decided that an individual semistructured interview would be more appropriate. Despite our small sample size, we believe that our study group is representative of patients with macular degeneration; although slightly older than the average patient seen in our low-vision clinic 23 (as patients with diagnoses other than age-related macular disease were excluded), our study population is similar in age to that found in epidemiological studies of prevalence of visual impairment. 24,25 Credibility of our study was assessed by a peer debriefing technique similar to that described by Ohman, 26 whereby the results were presented to a senior optometrist (Rachel Thomas) and a distinguished researcher in vision rehabilitation (GSR).…”
Section: Discussionmentioning
confidence: 87%
“…A retrospective analysis of patients attending the low vision service at Moorfields Eye Hospital, London, between 1973 and 2003, showed a rapid increase in the percentage of illuminated hand magnifiers being dispensed. 9 The increase was from 10 per cent in 1993 and 30 per cent in 1998 to 80 per cent of hand magnifiers in 2003. Although the percentage of stand magnifiers remained stable over this period, the proportion with internal illumination increased from approximately 50 to 80 per cent.…”
mentioning
confidence: 99%